Strategi Pengembangan Pertanian Padi Berbasis Local Economic Resources Development (LERD) (Studi pada Kecamatan Kedungtuban Kabupaten Blora Provinsi Jawa Tengah) - Ilham, Muchammad Abu (Jurnal Administrasi Publik, 2015)
Abstract: Strategy of Rice Agriculture Development Based On Local Economic Resources Development (LERD) (Studies in Kecamatan Kedungtuban Kabupaten Blora Central Java). Blora has the good potential in agriculture rice. The development of rice farming in Blora investigated by adopting the concept of Local Economic Development Resources (LERD). LERD concept is supported by Scaling calculations to determine the location of research and SWOT analysis to provide an overview of alternative strategies in agriculture development in Blora. This study was conducted using a descriptive study with qualitative approach. This study focuses on the potential of rice farming seen from several categories of ratios, namely Potential Production Land (PLhP), Rice Intensity (ITP), Wetland irrigation (KLS), and Land Productivity. Fourth ratio is calculated by the Scaling method. Government Strategic Plan of Blora seen from Scaling and LERD concept. Then factors - factors supporting and inhibiting the development of the agricultural sector is seen from the Scaling and SWOT analysis. The development of rice farming in Blora can be supported by the optimization of the agricultural budget in both the district and village levels, cooperative with academia for research as a reference for policy makers, as well as the further development can be done by seeking agribusiness which made of rice, thus increasing the chances of local economic development in Blora. Keywords: strategy, LERD, Scalling, Rice Farming. Abstrak: Strategi Pengembangan Pertanian Padi Berbasis Local Economic Resources Development (Studi pada Kecamatan Kedungtuban Kabupaten Blora Provinsi Jawa Tengah). Kabupaten Blora memiliki potensi unggulan pertanian padi. Pengembangan pertanian padi di Kabupaten Blora diteliti dengan mengadopsi konsep Local Economic Resources Development (LERD). Konsep LERD didukung dengan perhitungan Scaling untuk menentukan lokasi penelitian dan analisis SWOT untuk memberikan gambaran strategi alternatif dalam pengembangan pertanian di Kabupaten Blora. Penelitian ini dilakukan menggunakan jenis penelitian deskriptif dengan pendekatan kualitatif. Penelitian ini berfokus pada Potensi pertanian padi dilihat dari beberapa kategori rasio, yakni Potensi Lahan Produksi (PLhP), Intensitas Tanaman Padi (ITP), Keteririgasian Lahan Sawah (KLS), dan Produktivitas Lahan. Keempat rasio tersebut dihitung dengan metode Scaling. Rencana Strategi Pemerintah Kabupaten Blora dilihat dari Scaling dan Konsep LERD. Kemudian faktor â€“ faktor pendukung dan penghambat pengembangan pertanian dilihat dari hasil Scaling dan analisis SWOT. Pengembangan pertanian padi di Kabupaten Blora dapat ditunjang dengan optimalisasi anggaran pertanian baik ditingkat Kabupaten maupun Desa, kerja sama dengan akademisi dalam riset sebagai referensi pengambil kebijakan, serta mengupayakan agribisnis yang berbahan padi sehingga memperbesar peluang pengembangan ekonomi lokal di Kabupaten Blora. Â  Kata kunci: strategi, LERD, Scalling, Pertanian Padi.Â